Effectiveness Of Powtoon For Bhinneka Tunggal Ika Elements Based On A Saintific Approach In Class IV - Reinita; Mihalova, Dinara (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research is motivated by the use of technology-based media which is rarely used, the media used by teachers uses conventional media and abstract media. This study aims to develop Powtoon Video learning media based on a Class IV Scientific Approach. This research is a development research (R&D) using the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The results of the effectiveness of the pilot school at SDN 25 Air Tawar Selatan topic A were 60% pre test, 84.7% post test. Topic B pre test 53.52%, post test 85.29%. and the school where the research was conducted at SDN 29 Ulak Karang Utara Topic A pre test 55%, post test 82.5%. Topic B pre test 62.5%, post test 85% and SDN 01 Ulak Karang Selatan Topic A pre test 54.47%, post test 84.41%. Topic B pre test 54.11%, post test 84.11%. the results of the pre test and post test there is an increase in results. It can be concluded that the use of Powtoon Video for Unity in Diversity Elements Based on a Grade IV Scientific Approach is very effective in the learning process.